South Africa’s constitutional development: a matter of Machiavelli’s Prince and Hobbes’ Leviathan rather than Montesquieu’s Spirit of the laws? - Labuschagne, Pieter (Faculty of the Humanities, University of the Free State, 2010)
The democratisation and constitutional development of South Africa from a dominant parliament to a new constitutional order with a supreme constitution, was a significant development in the country’s constitutional development. However, the adoption of a supreme constitution is not necessarily an indication that a country has been fully democratised. In this article it is suggested that the level of a country’s democracy could also be measured by identifying the source or object of authority that enjoys the broadest legitimacy in society. This source or object of legitimacy will give an indication of the level of a state’s political and democratic maturity and consolidation. In an effort to measure South Africa’s level of democratic maturity and consolidation a theoretical framework was developed in the article that was based on the assumptions of Ken Wilber and Max Weber. The article points out that it is very important for further political development and democratic maturity in a state that the source or object of authority should be located on the second tier that consists of legal-rational rules. However, it seems that the majority of support in South Africa is based on the first tier, which predominately exists of a pre-rational level that focuses on traditional and charismatic authorities.
Keywords: Constitutional development; Constitution of the Republic of South Africa, 1996; Democracy; Wilber, Ken; Weber, Max